Advances in cross-cultural decision making - Schmorrow, Dylan, 1967-; Nicholson, Denise, 1967- (Boca Raton, Fl. : CRC Press, 2011)
'Preface This book is concerned with how decisions are made within a specific culture and across different cultures. The primary focus of the Cross Cultural Decision Making field is specifically on the intersections between psychosocial theory provided from the social sciences and methods of computational modeling provided from computer science and mathematics. While the majority of research challenges that arise out of such an intersection fall quite reasonably under the rubric of'human factors', although these topics are broad in nature, this book is designed to focus on crucial questions regarding data acquisition as well as reconciliation of mathematical and psychosocial modeling methodologies. The utility of this area of research is to aid the design of products and services which are utilized across the globe in the variety of cultures and aid in increasing the effectiveness of cross-cultural group collaboration. Each of the chapters of the book were either reviewed by the members of Editorial Board or germinated by them. This book would of special value to researchers and practitioners in involved in the design of products and services which are marketed and utilized in a variety of different countries'--
Includes bibliographical references.
Keywords: Decision making -- Cross-cultural studies; Decision making -- Mathematical models